Genetic variation of acquired structural chromosomal aberrations - Vodicka, Pavel; Musak, Ludovit; Vodickova, Ludmila; Vodenkova, Sona; Catalano, Calogerina; Kroupa, Michal; Naccarati, Alessio; Polivkova, Zdena; Vymetalkova, Veronika; Försti, Asta; Hemminki, Kari (Mutation research. Genetic toxicology and environmental mutagenesis, 2018)
Human malignancies are often hallmarked with genomic instability, which itself is also considered a causative event in malignant transformation. Genomic instability may manifest itself as genetic changes in the nucleotide sequence of DNA, or as structural or numerical changes of chromosomes. Unrepaired or insufficiently repaired DNA double-strand breaks, as well as telomere shortening, are important contributors in the formation of structural chromosomal aberrations (CAs). In the present review, we discuss potential mechanisms behind the formation of CAs and their relation to cancer. Based on our own studies, we also illustrate how inherited genetic variation may modify the frequency and types of CAs occurring in humans. Recently, we published a series of studies on variations in genes relevant to maintaining genomic integrity, such as those encoding xenobiotic-metabolising enzymes, DNA repair, the tumour suppressor TP53, the spindle assembly checkpoint, and cyclin D1 (CCND1). While individually genetic variation in these genes exerted small modulating effects, in interactions they were associated with CA frequencies in peripheral blood lymphocytes of healthy volunteers. Moreover, we observed opposite associations between the CCND1 splice site polymorphism rs9344 G870A and the frequency of CAs compared to their association with translocation t(11,14). We discuss the functional consequences of the CCND1 gene in interplay with DNA damage response and DNA repair during malignant transformation. Our review summarizes existing evidence that gene variations in relevant cellular pathways modulate the frequency of CAs, predominantly in a complex interaction. More functional/mechanistic studies elucidating these observations are required. Several questions emerge, such as the role of CAs in malignancies with respect to a particular phenotype and heterogeneity, the formation of CAs during the process of malignant transformation, and the formation of CAs in individual types of lymphocytes in relation to the immune response.
Keywords: Neoplasms; oprava DNA; nádory; Genetics; Chromosomal aberrations; Humans; DNA Damage; Cyclin D1; lidé; Xenobiotic metabolizing enzymes; poškození DNA; DNA repair; chromozomální aberace; Polymorphism, Genetic; Chromosome Aberrations; polymorfismus genetický; Mitotic checkpoints; DNA Repair